PENGARUH DEBT TO EQUITY RATIO, CURRENT RATIO, DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON EQUITY PADA PERUSAHAAN SUB SEKTOR TELEKOMUNIKASI DI BURSA EFEK INDONESIA TAHUN 2017-2024 - Annazmi Nisa, Sifa; Arismutia, Salza Adzri (JURNAL LENTERA BISNIS, 2026)
The purpose of this study is to assess the impact of Debt to Equity Ratio (DER), Current Ratio (CR) and Total Asset Turnover (TATO), on Return on Equity (ROE) in telecommunication subsector companies listed on the Indonesia Stock Exchange between 2017 and 2024. Secondary data from annual financial reports are used using quantitative methodology and associative techniques. Purposive sampling was used to select 80 observations from 10 companies as the research sample. Using IBM SPSS, this study was conducted by utilizing multiple linear regression, descriptive analysis, and classical assumption testing. The findings show that CR and TATO have no effect on ROE, while DER has a partial and significant impact. These three factors have a significant impact on ROE simultaneously, indicating that funding structure is crucial for increasing shareholder returns.